TOPICAL THERAPY OF OROPHARYNGEAL INFECTIOUS AND INFLAMMATORY DISEASES - E.N. Kotova (Вопросы современной педиатрии)
Antibacterial drugs are frequently used for the treatment of oropharyngeal infectious and inflammatory diseases despite the fact that in 80% of all the cases these diseases in childhood have viral etiology. Unjustified application of the antibiotics is one of the causes increasing in antibacterial resistance. The author considers the possibility of topical medicines usage in treatment of oropharyngeal inflammatory diseases. The recommendations on topical drug with antiseptic and anaesthetic effects are given in the article.